Unruptured tubal ectopic pregnancy with very high levels of beta HCG: a rare case report - Rajmane, Shantanu H.; Ubale, Sunita M.; Anand, Mamta N.; Senapati, J. B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
When the fertilized ovum is implanted outside the endometrial cavity, it is termed as ectopic pregnancy. The most common site being fallopian tube. The commonest site to be affected is ampulla of the fallopian tube followed by isthmus. Fimbrial and interstitial are rare sites for ectopic pregnancy. The incidence of ectopic pregnancy is increased over couple of decades. Important causes include PID, previous history of ectopic pregnancy, h/o tubal reconstructive surgery, h/o artificial reproductive techniques like IVF, use of IUD’s, h/o of tubal ligation etc. Fallopian tubal ectopic usually ruptures at duration of 7-8 weeks gestation. A ruptured tubal ectopic pregnancy can lead to massive haemorrhage leading to tachycardia, hypotension endangering life, which requires emergency surgical intervention & transfusion blood and blood products. Ectopic pregnancy with beta HCG <5000 IU/L, Gestational sac <4 cm, & vitally stable, can be managed medically with methotrexate, whereas higher levels of beta HCG, Gestational sac > 4 cm with live ectopic pregnancy and vitally unstable becomes obstetric emergency which should be managed surgically. Thorough clinical examination, use of ultrasonography and beta HCG levels, helps in timely diagnosis and management of ectopic pregnancy which can be lifesaving. This is a rare case report of unruptured live fimbrial ectopic pregnancy with very high levels of beta HCG (>50,000 mIU/ml), which was managed surgically.